Dua ribu dua mutiara hadits - T. M. Hasbi Ash-Shiddieqy (Bulan Bintang, 1975)
tr, Jil. 1=c.1-2; jil.2=c.1-3; jil.3=c.1; jil.5=c.1; jil.6=c.1-3; jil.7=c.1-7/oen, jil.7,c.8/tr, jil.1=c.3; sn,jl.1,c.4; jl.2,c.4; jl.5,c.2; jl.6,c.4-5; jl.7,c.9/ir,jil.7,c.10/ir, jil.2,c.5 ; jil.6,c.6-7